Improving Bio-Slurry Marketing Strategies In KPSP (Dairy Farmer Cooperative) - Ariyanto; Yudi (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
The utilisation of bio- slurry can improve sustainable agriculture and encourage increased community income, especially for dairy farmers at KPSP Setia Kawan Nongkojajar (www.kpspsetiakawan.com), Pasuruan, East Java, Indonesia which is a cooperative body for dairy farmers one of the largest in Indonesia where some of the farmers have processed livestock waste into biogas with a total of approximately 1547 biogas installation units and will continue to grow considering the number of dairy farmer membersat KPSP Setia Kawan Nongkojajar about 7000 members. Therefore, in this study, the author aims to find the right bio-slurry marketing strategy to stimulate sustainable agriculture through processing livestock waste into biogas and bio-slurry. According to Li and Liu (2020), SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is a business analysis technique used to evaluate the strengths, weaknesses, opportunities, and threats a company or organisation faces. The data collection method used in this research is interviews and questionnaires to 3 respondents who are represented by one of the heads of breeders at KPSP Setia Kawan Nongkojajar, biogas officers and third-party collectors, namely PT Pupuk Suburkan Negeri (PSN) as the first buyer of bio-slurry from KPSP Setia Kawan Nongkojajar, Pasuruan, East Java, Indonesia by interviewing and filling out questionnaires to the three respondents for data collection in May 2023. The results of the research and discussion found that the bio-slurry marketing strategy at KPSP (Dairy Farmer Cooperative) Setia Kawan Nongkojajar Pasuruan, East Java, Indonesia is an SO (Strenght and Opportunity) strategy is a marketing strategy that optimizesopportunities with the strengths possessed by KPSP (Dairy Farmer Cooperative) Setia Kawan Nongkojajar, Pasuruan, Indonesia with a total score of Strength 0.69 and Weakness 0.31 as IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) analysis Opportunity 0.51 and Treath 0.49 and quadrant EFE and IFE obtained Opportunity: 0.26, Y : Total (O-T), and X : Total (S-W) 0.66 Strength.